Idiopathic generalised epilepsies of adult onset: a reappraisal and literature review*. Issue 3 (18th July 2018) - Pimentel, José; Varanda, Sara; Guimarães, Pedro; Lopes da Silva, Fernando
ABSTRACT: Idiopathic generalised epilepsies are characterised by widespread, symmetric, bilateral spike‐and‐wave discharges on EEG. Onset typically occurs in children and adolescents, but may also start in adulthood. These forms of adult onset constitute the focus of this review. A critical analysis of the medical literature was conducted through a narrative review search of PubMed and Medline databases. Cases of idiopathic generalised epilepsies with adult onset, in general, are not considered to be independent nosological entities. The "grand mal on awakening" seems to prevail among the idiopathic syndromes of adult onset. The EEG findings that question the diagnosis of late‐onset idiopathic generalised epilepsies consist mainly of patterns interpreted as representing focal epileptiform activity. Normal brain MRI and typical EEG abnormalities are essential for diagnosis. For all cases with symptomatology of suspected adult‐onset idiopathic generalised epilepsy, it is mandatory to exclude neurological conditions that may be associated with epileptic seizures which appear in this age group. A correct diagnosis of adult‐onset idiopathic generalised epilepsy alleviates concern for a symptomatic origin, leading to appropriate antiepileptic treatment.